Merchants, Landlords, Magistrates The Depont Family in Eighteenth-Century France - Forster, Robert (Johns Hopkins University Press, 2019)
Originally published in 1980. A social historian of modern France, Robert Forster discovered a series of father-to-son letters that presented an unusual opportunity to trace in human terms the impact of institutions and cultural norms on eighteenth-century French society. From these letters and other family papers, Forster reconstructed a family biography of the Deponts of La Rochelle over four generations. Their story affords new insights into the workings of institutions-economic, religious, legal, administrative-the mentality of provincial notables, the world of Parisian high finance and salon society, and the response of a socially mobile family to the challenges of the century, climaxing in the French Revolution of 1789. Forster demonstrates how real people in an upwardly mobile family coped with their changing society, moved from overseas trade to local and then national office, managed their wealth, treated their children, and then parried the psychological shocks accompanying their ascent to status and power. It is the story not of a "class" response to abstract trends or forces identified by the historian in retrospect but of flesh-and-blood human beings grappling with day-to-day decisions and revealing a full range of human ambiguity and inconsistency. This study offers perspective on the emergence by 1800 of a new elite in France-a social amalgam of landlords, administrators, and professional men, inculcated with a national awareness and a cautious political liberalism. These were the notables who would govern France in the next century. Forster's approach, uncommon among social historians, combines narrative and analytical modes of historiography. Based on archival materials in La Rochelle and Paris, the book blends economic, social, cultural, and political history.